EFEKTIFITAS EDUKASI KESEHATAN GIGI MENGGUNAKAN PERMAINAN TRUTH OR DARE TERHADAP TINGKAT KETERAMPILAN MENYIKAT GIGI PADA SISWA-SISWI SD NEGERI 106166 MARINDAL II KECAMATAN PATUMBAK DELI SERDANG - sondang; Asnita Bungaria Simaremare (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Dental health is important for individuals, including children. Childhood is a very important time to maintain healthy teeth. The condition of the milk teeth (deciduous) really determines the condition of the replacement teeth, therefore it is very important to maintain dental health at this time. Dental health education using the truth or dare game media can have an impact on increasing students' knowledge, attitudes and actions to maintain the health of their teeth and mouth. The aim of this research is to determine the effectiveness of dental health education using the truth or dare game on the level of toothbrushing skills in elementary school students. The type of research carried out was descriptive analytical research using the quasi-experimental method which was carried out at SD Negeri 106166 Marindal II, Patumbak Deli Serdang District. This research will be carried out from June to October 2023 with a sample size of 30 people. The results of this research, the average level of tooth brushing skill before being given dental health education using the truth or dare game to students was 12.3 and the average after being given dental health education using the truth or dare game was 15.8. There is the effectiveness of dental health education using the truth or dare game on the level of tooth brushing skills among students at SD Negeri 106166 Marindal II, Patumbak Deli Serdang District in 2023 with a p-value of 0.000<0.05. It is hoped that this research can increase students' insight and knowledge about toothbrushing skills.